Self-efficacy and university digital competence in times of Covid-19 - Arpasi Bejarano, Diego Alberto (2022)
The objective of this study was to determine the relationship between self-efficacy and digital competence of university students at a public university in the city of Lima. For its realization, a non-experimental design of correlational level was chosen. The sample consisted of 110 students selected by convenience sampling. Two instruments were applied to evaluate the study variables, whose validity was determined by expert judgment. A pilot test was carried out to be able to resolve the internal consistency of the instruments of each of the variables using Cronbach's alpha, the results determined reliability coefficients of 0.915 and 0.961 for self-efficacy and digital competence respectively, which indicates that the information collected by the resulting instruments be reliable enough for the progress of the investigation. The results show the existence of a significant direct weak relationship between self-efficacy and digital competence. It was concluded that high levels of self-efficacy are related to high levels of digital competence.